MEMAHAMI PARAGRAF EKSPOSISI MELALUI TEKNIK MEMBACA KRITIS SISWA SEKOLAH MENEGAH PERTAMA - Idrus Ahmad; Idwan Djais (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
This Classroom Action Research (CAR) aims to analyze and describe the ability to understand expository paragraphs through critical reading techniques in eighth-grade students at SMP Negeri 1 Mangoli Selatan. By combining qualitative and quantitative analysis methods, the research results are analyzed and described as follows: The results indicate that critical reading techniques can improve the reading skills of eighth-grade students at SMP Negeri 1 Mangoli Selatan, both in terms of process and outcomes. In terms of process, students enthusiastically participated in the lesson, reading and quickly comprehending the texts presented by the teacher. In terms of outcomes, the learning showed that the average score in cycle I, which was 74.12%, increased to 79.84% in cycle II, meeting the minimum completion criteria of 78.00. Thus, it can be concluded that the research in cycle II has achieved the Minimum Completion Minimum (KKM) and will not be continued in the next cycle.